2014
DOI: 10.1016/j.jdiacomp.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of serum pigment epithelium-derived factor in type 2 diabetes patients

Abstract: Aim To determine if serum pigment epithelium-derived factor (PEDF) levels in Type 2 diabetes are related to vascular risk factors and renal function. Methods PEDF was quantified by ELISA in a cross-sectional study of 857 male Veterans Affairs Diabetes Trial (VADT) subjects, and associations with cardiovascular risk factors and renal function were determined. In a subset (n=246) in whom serum was obtained early in the VADT (2.0 ± 0.3 years post-randomization), PEDF was related to longitudinal changes in renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Surface plasmon resonance analysis demonstrated that emetine binds to PEDF receptor ATGL with high-binding affinity (KD = 14.3 nmol/L) ( Figure 3A). (33), and PEDF levels are significantly associated with various metabolic diseases (25,(34)(35)(36). In the present results from murine streptozotocininduced diabetes, PEDF and TNF levels are significantly increased in pancreas, and expression significantly correlated with blood glucose levels.…”
Section: Emetine Binds Atgl With High Affinitysupporting
confidence: 52%
“…Surface plasmon resonance analysis demonstrated that emetine binds to PEDF receptor ATGL with high-binding affinity (KD = 14.3 nmol/L) ( Figure 3A). (33), and PEDF levels are significantly associated with various metabolic diseases (25,(34)(35)(36). In the present results from murine streptozotocininduced diabetes, PEDF and TNF levels are significantly increased in pancreas, and expression significantly correlated with blood glucose levels.…”
Section: Emetine Binds Atgl With High Affinitysupporting
confidence: 52%
“…Pigment epithelial-derived factor (PEDF) is a serpin-like protein lacking inhibitory function that was selected for study because expression is known to be influenced by diabetes and obesity [ 2 , 3 ], circulating levels are related to vascular complications of diabetes and insulin sensitivity [ 4 – 6 ], and it is produced by adipose tissue, liver, and placenta [ 7 9 ]. One prior report found PEDF expression decreased in placentae from stillborn [ 10 ] and a pilot study noted increased cord blood levels in pre-eclampsia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, circulating levels of PEDF demonstrate opposite changes. Several groups including us have reported that serum PEDF levels are significantly increased in patients with T1DM [81, 82] and T2DM [83, 84]. The elevated PEDF levels are positively associated with body mass index, lipid levels and vascular dysfunction [83].…”
Section: The Mechanism Underlying Abnormal Angiogenesis In Diabetesmentioning
confidence: 99%
“…Several groups including us have reported that serum PEDF levels are significantly increased in patients with T1DM [81, 82] and T2DM [83, 84]. The elevated PEDF levels are positively associated with body mass index, lipid levels and vascular dysfunction [83]. The elevated serum levels of PEDF are also found in patients with obesity [85] and metabolic syndrome [86] and in T2DM animal models [40, 87].…”
Section: The Mechanism Underlying Abnormal Angiogenesis In Diabetesmentioning
confidence: 99%